Involvement of distant octacalcium phosphate scaffolds in enhancing early differentiation of osteocytes during bone regeneration. (15th July 2021) - Saito, Shizu; Hamai, Ryo; Shiwaku, Yukari; Hasegawa, Tomoka; Sakai, Susumu; Tsuchiya, Kaori; Sai, Yuko; Iwama, Ryosuke; Amizuka, Norio; Takahashi, Tetsu; Suzuki, Osamu
Abstract: This study hypothesized that distant octacalcium phosphate (OCP) scaffolds may enhance osteocyte differentiation in newly formed bone matrices. The results obtained were compared with those of Ca-deficient hydroxyapatite (OCP hydrolyzate, referred to as HL hereafter). Granular OCP and HL, 300–500 µm in diameter, were implanted in critical-sized rat calvarial defects for eight weeks and subjected to histology, immunohistochemistry, histomorphometry, and transmission electron microscopy (TEM). Early osteocyte differentiation from an osteoblastic cell line (IDG-SW3) was examined using materials without contacting the surfaces for 10 days. The material properties and the medium composition were analyzed through selected area electron diffraction (SAED) using TEM observation and curve fitting of Fourier transform infrared (FT-IR) spectroscopy. The number of positive cells of an osteocyte earlier differentiation marker podoplanin (PDPN) in bone matrices, along the direction of bone formation, was significantly higher in OCP than that in HL. The ultrastructure around the OCP surfaces observed by TEM showed the infiltration of some cells, including osteocytes adjacent to the OCP surface layers. The OCP structure remained unchanged by SAED analysis. Nanoparticle deposition and hydrolysis on OCP surfaces were detected by TEM and FT-IR, respectively, during early osteocyte differentiation in vitro . The medium saturation degree varied in accord with ionic dissolution, resulting in possible hydroxyapatite formation on OCP but not on HL. These results suggested that OCP stimulates early osteocyte differentiation in the bone matrix from a distance through its metastable chemical properties. Statement of significance: This study demonstrated that octacalcium phosphate (OCP) implanted in critical-sized rat calvaria bone defects is capable of enhancing the early differentiation of osteocytes embedded in newly formed bone matrices, even when the surface OCP is separated from the osteocytes. This prominent bioactive property of OCP was demonstrated by comparing the in vivo and in vitro performances with a control material, Ca-deficient hydroxyapatite (OCP hydrolyzate). The findings were elucidated by histomorphometry, which analyzed the differentiation of osteocytes along the parallel direction of new bone growth by osteoblasts. Therefore, OCP should stimulate osteocyte differentiation through ionic dissolution even in vivo owing to its metastable chemical properties, as previously reported in an in vitro study (Acta Biomater 69:362, 2018). Graphical abstract: Image, graphical abstract